Analysis of Quick Ratio, Return on Assets, and Company Size in Pulp and Paper Companies - Wahyu Indah Mursalini; Afniyeni Afniyeni; Mutiara Dwi Santika (Transpublika Publisher, 2024)
This research aims to analyze the influence of the Quick Ratio and Return on Assets on company size in the Pulp and Paper industry sector on the Indonesian Stock Exchange over a five-year period from 2017 to 2022. The study included 8 samples taken from 9 various groups of companies within the pulp and paper sub-sector listed on the IDX during the specified timeframe. The research utilized purposive sampling for data collection. The analysis involved classical assumption testing, coefficient of determination test (R²), multiple linear regression, and hypothesis testing. The research results show that partially the Quick Ratio has no significant effect on Company Size. Meanwhile, Return on Assets has no significant effect on Company Size. After conducting the F test to analyze the third hypothesis, it was determined that the f value of 7.711 is greater than the f table of 3.209. Additionally, the significance value of 0.001 is less than the pre-determined alpha level of 0.05. This suggests that there is a significant impact of the independent variable on the dependent variable, namely the Quick Ratio and Return on Assets which together have an effect significant to Company Size. In this research, the Quick Ratio and Return on Asset variables can only explain 25.5% of company size according to the results of the coefficient of determination (R²) test, so the closeness of the dependent and independent variables is low. Meanwhile, the remaining 74.55% is influenced by other variables outside the model discussed in this research.